Communication Strategy Customer Relations Officer PT Dwitunggal Putra Pegadai Tangerang Branch in Handling Customer Complaints - Sagiyanto, Asriyani; Mawadda, Ayu Andini; Rahmah, Ade; Utomo, Ardian Setio (P3KM Politeknik Pertanian Negeri Samarinda, 2024)
Customer Relations Officers are a bridge between customers and the company, especially in handling customer complaints. This research aims to determine the company customer relations office strategy PT Dwitunggal Putra Pegadai Tangerang branch in handling customer complaints. This study used a descriptive qualitative method. This research shows that Customer Relations Officers are essential in handling customer complaints and creating customer satisfaction. The Customer Relations Officer's process in resolving customer complaints can be carried out from the start, namely identifying existing problems, what complaints the customer is complaining about, developing a plan to resolve the complaint, and then acting and communicating efforts to improve customer complaints. Moreover, this is the re-evaluation stage of whether the Customer Relations Officer has resolved the problem. Apart from that, it also carries out several strategic steps in relations with customers namely Fact-finding which is it appears that accurate data and evidence support problems, Planning and Programming which the company creates a way that can connect between companies with customers, Taking Action and Communicating which the company prioritizes a personal approach to consumers and Evaluation which the company gets a good score from CSI in terms of customer satisfaction. The company can resolve the problems included in the service mechanism.